อนาคตภาพรูปแบบสังคมแห่งการเรียนรู้เพื่อการปรับเปลี่ยนกระบวนทัศน์เชิงบวกสำหรับชุมชน - สุวิธิดา จรุงเกียรติกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The research on "the scenario of a learning society model toward a positive paradigm shift for communities" is a prospective qualitative research where the EDFR (Ethnographic Delphi Futures Research) technique is used. The research aims to: 1) analyze and synthesize learning society model that promotes a positive paradigm shift for communities from both local and global literatures, academic articles and research studies from 1997 to 2011; 2) explore the experts’ perspectives on the development of a learning society toward a positive paradigm shift for communities from the in-depth interviews with thirty-two experts and the study visits of five best practices; 3) develop a learning society model toward a positive paradigm shift for communities; and 4) propose the scenario of a learning society model toward promoting a positive paradigm shift for communities. The group discussions, held to review and evaluate the research results, were joined by twenty experts. There were two focus group discussions, one for the ten experts at the policy levels and another one for the ten experts at the operational levels. The research included the total samples of fifty-two persons. The learning society model toward promoting a positive paradigm shift for communities consists of five main components: 1) the components of a learning society toward a positive paradigm shift for communities, 2) the principles for development of a learning society toward a positive paradigm shift for communities, 3) the development processes of a learning society toward a positive paradigm shift for communities, 4) the strategies for the development of a learning society toward a positive paradigm shift for communities, and 5) key success factors. All components comprise details that can really be put into practice. The learning society model that promotes a positive paradigm shift for communities should be freely implemented, in natural ways, by the communities. The model should ideally be dynamic and developed on a continuous basis. The lifelong learning and the knowledge sharing culture are among essential elements of the learning society model. The communities may appropriately apply the knowledge gained from this research in accordance with their contexts and social conditions. The scenario of a learning society model toward a positive paradigm shift for communities will help enhance learning processes among individuals, groups of individuals and social networks in valuable ways. The model will also lead all parties to reach the existing truth, virtue and goodness. It can also raise the people’s ability to freely learn in creative ways. Further, the model will eventually cause the ways of thinking, beliefs, social value and learning to be changed in positive ways. Then, the people will live in good and positive frame of mind that should enable them to overcome any problems and meet overall needs in balanced, sustainable and happy ways. With positive paradigm shifts, the communities will see the right way of development encouraging the community members to live in harmony. Finally, the scenario of a learning society model toward promoting a positive paradigm shift for communities as the guideline for action ensures the enhancement of the quality of life of the individual and moves the communities and societies toward the sound equilibrium, fairness and sustainability.